Neuropsychological profile of delusional disorder - Leposavić, Ivana (Array, 2009)
Previous studies concerned with neuropsychological aspect of delusions, were mainly focused on specific forms of this disorder, such as Cotard or Capgras type of delusions. Comparatively small numbers of investigations were concerned with cognitive deficiencies accompanying the delusions. The substance of this study includes the detection of neuropsychological dysfunctions in patients with delusional disorder, and tracing of these cognitive distortions to appropriate brain regions. The neuropsychological profile of patients with delusional disorder includes impediment of complex attention modalities. From this primary disorder, there also stems a disorder of verbal memory in the sense of reduced recognition